Match-related risk factors for injury in male professional football - Bengtsson, H. (Linköping University, Department of Medical and Health Sciences, Division of Physiotherapy, 2017)
Background: Injuries are common in professional football, especially during matches, and they cause suffering for players, in both the short and the long term. It is therefore important to try to prevent these injuries. One of the most important steps in injury prevention is to fully understand the different risk factors that contribute to these injuries.